Diurnal time budget of wintering Teal Anas crecca at Lac des Oiseaux, northeast Algeria - Houhamdi, M; Samraoui, B (Wildfowl, 2001)
This paper investigates the spatial distribution and the diurnal time budget of wintering Teal Anas crecca over a period of four years at a shallow lake, Lac des Oiseaux, northeast Algeria. The lake is exploited by Teal as a diurnal roost for both resting and feeding. The spatial distribution of Teal within the lake may be affected by drought but appeared to vary little over the study period. However, wintering Teal displayed a strong seasonal shift in behavior [sleeping, feeding, preening, swimming, flying], probably to meet changes in energy requirements. Lac des Oiseaux and neighboring Mekhada marsh appear to act as a 'functional unit' for wintering ducks. The results highlight, in part, the need to afford legal and effective protection to the whole Numidian wetland complex. Degradation of the Mekhada marshland, threatened by dam construction, may well make Lac des Oiseaux, a Ramsar site, an unfavorable habitat for wintering ducks.